Association between preoperative anxiety and postoperative pain intensity among women undergoing cesarean section - Komalasari Komalasari; Umi Latifa; Elsy Juni Andri Kariny; Riona Sanjaya (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Preoperative anxiety is a common psychological response among women undergoing cesarean section and may increase postoperative pain perception through physiological and psychological stress responses. Identifying the relationship between anxiety and pain is essential for improving perioperative maternal care. Purpose: To determine the relationship between preoperative anxiety levels and postoperative pain intensity among women undergoing cesarean section at RSIA Mutiara Hati. Methods: This quantitative study employed an analytical cross-sectional design. A total of 74 post-cesarean section patients were recruited using purposive sampling. Preoperative anxiety was assessed using the Hamilton Anxiety Rating Scale (HARS), while postoperative pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using descriptive statistics and the Gamma correlation test with a significance level of p < 0.05. Results: Most respondents experienced severe preoperative anxiety (54.1%) and severe postoperative pain (51.4%). Statistical analysis demonstrated a significant relationship between preoperative anxiety and postoperative pain intensity (p = 0.015). Women with higher preoperative anxiety were 4.09 times more likely to experience greater postoperative pain intensity (OR = 4.091; 95% CI = 1.315–12.728). Conclusion: Preoperative anxiety was significantly associated with postoperative pain intensity among women undergoing cesarean section. Early identification and management of anxiety through preoperative education, therapeutic communication, and psychological support may help reduce postoperative pain and improve maternal recovery.